2020
DOI: 10.1080/2159676x.2020.1713204
|View full text |Cite
|
Sign up to set email alerts
|

Researching retired ex-servicemen: reflections on ethnographic encounters

Abstract: The University of Gloucestershire accepts no liability for any infringement of intellectual property rights in any material deposited but will remove such material from public view pending investigation in the event of an allegation of any such infringement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Reflexivity is a useful tool in maintaining this fine balance, in which ethnographers engage in a process of critical reflection, acknowledging the links between their biographies, assumptions, and research approaches, and become increasingly aware of their position in the field and how this can influence the research setting (Pringle and Thorpe, 2017;Davies, 1999). For example, it has been suggested that shared identity characteristics between the researcher and research participants may facilitate the processes of gaining trust, access, and establishing and maintaining a rapport, with some researchers only ever being able to achieve superficial acceptance because of identity differences (Gurney, 1985;Williams et al, 2021). However, this notion has been challenged as individuals can connect with many different intersecting identities and societal groups and, considering race, gender, age and class, it is challenging for an ethnographer to easily align themselves across all these features (Alcoff, 1991;Chadderton, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reflexivity is a useful tool in maintaining this fine balance, in which ethnographers engage in a process of critical reflection, acknowledging the links between their biographies, assumptions, and research approaches, and become increasingly aware of their position in the field and how this can influence the research setting (Pringle and Thorpe, 2017;Davies, 1999). For example, it has been suggested that shared identity characteristics between the researcher and research participants may facilitate the processes of gaining trust, access, and establishing and maintaining a rapport, with some researchers only ever being able to achieve superficial acceptance because of identity differences (Gurney, 1985;Williams et al, 2021). However, this notion has been challenged as individuals can connect with many different intersecting identities and societal groups and, considering race, gender, age and class, it is challenging for an ethnographer to easily align themselves across all these features (Alcoff, 1991;Chadderton, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, this notion has been challenged as individuals can connect with many different intersecting identities and societal groups and, considering race, gender, age and class, it is challenging for an ethnographer to easily align themselves across all these features (Alcoff, 1991;Chadderton, 2012). In the published literature the identity markers and status relations of the researcher and the researched in ethnographic fieldwork is receiving more attention (Wheaton, 2002;Williams et al, 2021), but it has also been raised that, in maledominated spaces, there is little acknowledgement or visibility of the researchers' gendered identity in which 'maleness passes unquestioned' (Woodward, 2008, p. 548). Gottdiener (2005, p. 81) defines male-dominated environments as 'places where traditionally men have congregated more commonly than women and where males are at a distinct advantage regarding the deployment of power'.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation